Analysis of relationship between the intensity of the rainfall and floods during the December 2014 in Sungai Pahang Basin - Nur Ellani, Amir Shariffuddin (2016)
In December 2014, severe flooding had hit part of Peninsular Malaysia. As a result many casualty and damages, for Pahang state alone suffered losses of RM610 million. The main causes were the high intensity of rain and overflowing rivers to major settlements. The main objective of this study was to analyse the relationship between the intensity of the rain and floods during the December 2014 in Sungai Pahang basin. The specific objectives of the study are as follows; to validate satellite-based daily rainfall with rain-gauge rainfall and to analyse relationship between the intensity of the rainfall and floods. This study uses satellite-based daily rainfall, to map the spatial-temporal distribution of rainfall during flood events. The satellite-based daily rainfall over rain-gauge station retrieved and validated. Then, the analysis of intensity satellite-based daily rainfall data for each towns along the river Ulu Pahang and related areas was performed. The satellite-based and rain-gauge station daily rainfall data shows a good correlation (r= 0.79 - 0.92; coefficient= 0.72-1.67). From the analysis, the city experienced flooding even got a little rain intensity. This because the river overflowed due to the high intensity of rain in the upper reaches for example Merapoh, Kuala Tahan and Jerantut. In conclusion, the extreme rainfall event at the upstream area will cause the water level increase rapidly and unexpected flood will happen. The outcomes of this study shows satellite-based rainfall data could be used to help in prepare a flood incident report with more comprehensive.